2002
DOI: 10.4049/jimmunol.168.9.4788
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Ig-Fusion Proteins Into B Cells Prevents and Treats Autoimmune Diseases

Abstract: Based on the tolerogenic properties of IgG carriers and B cell Ag presentation, we developed a retrovirally mediated gene expression approach for treatment of autoimmune conditions. In this study, we show that the IgG-Ag retroviral constructs, expressing myelin basic protein (MBP) or glutamic acid decarboxylase in B cells, can be used for the treatment of murine models for multiple sclerosis and diabetes. Transduction of syngeneic B cells with MBP-IgG leads to the amelioration of ongoing experimental allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 27 publications
7
110
0
Order By: Relevance
“…When this Ig-fusion protein was delivered into bone marrow (BM)-derived cells or lipopolysaccharide (LPS)-stimulated B cells via retroviral infection, and then these cells were injected into syngeneic recipients, the recipients were rendered significantly hyporesponsiveness to specific epitopes of the antigen. [3][4][5][6][7][8][9][10] Results with this gene therapy protocol demonstrated that it was simple and effective, even in primed recipients and autoimmune animals, including preliminary studies with spontaneous diabetes in nonobese diabetic (NOD) mice. 6,10 However, the precise mechanism of tolerance induction in this system is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…When this Ig-fusion protein was delivered into bone marrow (BM)-derived cells or lipopolysaccharide (LPS)-stimulated B cells via retroviral infection, and then these cells were injected into syngeneic recipients, the recipients were rendered significantly hyporesponsiveness to specific epitopes of the antigen. [3][4][5][6][7][8][9][10] Results with this gene therapy protocol demonstrated that it was simple and effective, even in primed recipients and autoimmune animals, including preliminary studies with spontaneous diabetes in nonobese diabetic (NOD) mice. 6,10 However, the precise mechanism of tolerance induction in this system is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Results with this gene therapy protocol demonstrated that it was simple and effective, even in primed recipients and autoimmune animals, including preliminary studies with spontaneous diabetes in nonobese diabetic (NOD) mice. 6,10 However, the precise mechanism of tolerance induction in this system is not well understood. We know that tolerance does not involve a Th1/Th2 shift, 4,10 that major histocompatibility complex (MHC) class II expression on the presenting B cells is important and B cells are critical antigen-presenting cells (APCs), 7 but that Fc receptors are not required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…B cells transduced with a vector encoding PLP (100-154) as well as B cells expressing a MBP-Ig fusion protein were shown to ameliorate ongoing disease. 51,52 We have used a diploid, untransformed, transduced fibroblast line secreting PLP (101-157) to successfully treat EAE mice. 30 In addition, our protocol was designed to deliver a low-level, constant exposure to antigen, and this may be the reason we have never observed the anaphylactic response seen in some cases upon repeated injection of antigen.…”
Section: Discussionmentioning
confidence: 99%